Studies in Islamic traditions and literature - Tottoli, Roberto, author.
1 online resource (x, 273 pages).
Keywords: "A collection of articles and studies discussing early Islamic tenets and beliefs based on Islamic traditions and literature. A number of studies appears for the first time in English. The topics dealt with relates to the Islamic prostration in ritual prayer, other topics mainly dicussed through the analysis of hadith literature and reports and narratives related to the literary genre of the Qisas al-anbiya' (Stories of the Prophets). The readers of this collection of essays are scholars and students of early Islam, of the development hadith literature and of the narratives on Islamic prophets; all together the studies bring to light the dynamics between the formation of early traditions and their role in the origin and developments of Islamic literature"--